Kinetic Analysis of Controlled/“Living” Radical Polymerizations by Simulations. 2. Apparent External Orders of Reactants in Atom Transfer Radical Polymerization - Shipp, Devon A; Matyjaszewski, Krzysztof (Macromolecules, 2000)
Simulations of atom transfer radical polymerization (ATRP) have been used to examine the kinetics of these reactions. Because ATRP is subject to the persistent radical effect, the apparent external orders of various reactants are predicted to behave in a complex manner, generally not being simple first- or inverse-first orders. Addition of deactivating species at the beginning of the reaction results in the apparent external orders of the initiator and activator tending toward unity. Heterogeneity of the reaction system, where activator and/or deactivator may be only partially soluble, was also investigated. It was found that the ratio of soluble activator-to-soluble deactivator governed the rate of polymerization. The apparent external orders of the initiator and activator were found to be close to unity under the heterogeneous conditions simulated. Simulations of ATRP initiated with very efficient and fast initiators showed that these may lead to a substantial and irreversible buildup of deactivator species. This led to the conclusion that the rate of polymerization can be dependent upon the initiator used and, more generally, is dependent on the relative amount of deactivator available for reaction.